ANALISIS PERSUASI DALAM MELAKUKAN UPSELLING KAMAR PADA HOTEL ADIWANA UNAGI SUITES UBUD - Bisena, I Kadek Agus (Program Studi Akuntansi IKOPIN, 2022)
Upselling is a program to increase income at Adiwana Unagi Suites Ubud by introducing higher-level products. In the implementation of upselling, it must be supported by standards and procedures for implementation, knowledge of the language of persuasion, and knowledge of the products being sold. Adiwana Unagi Suites has a market that has more foreign tourists, so it is very important to master English which is used to direct tourists to increase sales. The research was conducted using a qualitative descriptive method with the research sample being the front office employees of Adiwana Unagi Suites. The results of the study indicate that in terms of standards and procedures it is very good and clear which describes how the steps in it are able to make someone interested in upselling. In terms of the English skills used by employees, it still shows deficiencies with an index of 74.2, while the product mastery index shows a very good score with an index of 93. From these results, it is expected that hotel management can take action to improve English skills so as to encourage improvement.